Mendudukkan Kembali Makna Ilmu dan Sains dalam Islam - Sofian Hadi; Ari Ashari (Tasfiyah: Jurnal Pemikiran Islam, 2020)
This article tries to explain the fundamental differences between science and knowledge. There has been a confusion of terms between them such as the usage of the term 'science' to indicate 'knowledge’ and vise versa. Semantic differences of the terms influence the confusion of meanings and terms agreed by scientists and language experts. Then the definitions of the both terms need to be explored and examined to avoid confusion and disordered thinking. Furthermore, the source of science is al-Qur'an and Hadith, while the fundamental source of knowledge is an empirical object. The recent advances in modern science and knowledge need to be observed, looking at what the Western civilization has done to separate religion and science because they have misunderstood the meaning of science which is could not be separated from religion.